Study on adaptability culture and project performance in project-based companies - Ahmad Salahuddin, Mat Hassan (2015)
This thesis is focus on culture in the organization where the factors which influence work performance. This study is to identify whether they have impact or effect between organizational cultures towards project performance in the organization. This thesis objectives are to identify culture implementation in organizational at construction project and also to identify the relationship between organizational culture and project performance. Using elements that includes in Denison model, there are a few factor that measurable to investigate organizational culture existence in the organization such as involvement element, consistency element, and also adaptability element. Meanwhile to measure project performance also have some elements which are time and cost. Both two variables will be studied whether it closely related between organizational culture and project performance. To determine relationship between these variables, several tests was done to identify impact between each other. Software Statistical Package for the Social Science (SPSS) was used as tool to analyze data achieved from respondents by using questioner. After several tests have completely been carried out, results showing relationship between work cultures have impact to project performance. This explicable by referring to value shown from SPSS software. Based on these values, assumption can make to formulate this thesis decision is work culture in one organization give impact to project performance.